Numerical Study of the Effect of Perforation Friction and Engineering Parameters on Multicluster Fracturing in Horizontal Wells. (1st September 2021) - Jiao, Zixi; Zhang, Anlin; Du, Longhuan; Yang, Yang; Fan, Hua
Abstract : Simultaneous multiple-fracture treatments in horizontal wellbores have become one of the key methods for economically and efficiently developing oil and gas resources in unconventional reservoirs. However, field data show that some perforation clusters have difficulty propagating fractures due to the internal mechanism of competing initiation and propagation among the fractures. In this paper, the physical mechanisms that influence simultaneous multiple-fracture initiation and propagation are investigated, and the effects of engineering parameters and in situ conditions on the nonuniform development of multiple fractures are discussed. A 3D fracture propagation model was established with ABAQUS to show the influence of the stress shadow effects and dynamic partitioning of the flow rate by simulating the propagation of multiple competing fractures generated in the perforation clusters. Based on the results of these simulations, simultaneous flow in multiple fractures can propagate evenly. Through adjusting the number of perforations in each cluster or the perforation diameter, the effect of the stress shadow can be significantly reduced by increasing the perforation friction, and the factors that affect the development of multiple fractures are changed, from the stress shadow effect to the dynamic partitioning of the flow rate. When the stress shadow effect is dominant, increasing the fracturing fluid viscosity promotes the uniform development of multiple fractures and increases the fracture width. When the dynamic partitioning of the flow rate is dominant, increasing the injection rate greatly affects the uniform development of multiple fractures.